Fatigue characteristics and environmental sustainability of rubber asphalt composite modified asphalt mixtures incorporating nanosilica. (5th September 2022) - Lushinga, Nonde; Dong, Zejiao; Cao, Liping; Yang, Chen; Ullah, Shafi
Abstract: Nano materials such as nanosilica have recently been used to modify the properties of rubberized asphalt mixtures. Depite the performance improvement of the modified mixtures, there are still concerns about nanosilica's pathways contributing to environmental problems. In light of these concerns, this research was conducted to evaluate the fatigue charcateristics and environmental sustainability of rubber asphalt composite modified mixtures incorporating nanosilica using the life cycle assessment (LCA) methodology. The fatigue performance prediction was determined by means of numerical simulation implemented in finite element (FE) dynamic implicit Abaqus code. The LCA was carried out in accordance with ISO 14, 040 standards and implemented in SimaPro 9.2.1 LCA commercial software. The FE model results showed that asphalt pavement with rubber asphalt/nanosilica composite modified asphalt mixture (herein composite mixture) had lower tensile strains at the bottom of asphalt layer as compared to the pavements with conventional rubberized asphalt mixtures (herein conventional mixture). This increased the fatigue life of the composite mixtures. The LCA results revealed that the composite mixtures had a global warming potential (GWP) of 5.92 x10 4 kg CO2 -Eq compared to 6.56 × 10 4 kg CO2 -Eq per functional unit for the conventional mixtures. Despite the reduction in GWP, composite mixture had a negative effect on the acidification potential of the impact category. Based on the research findings, the study concluded that nanosilica can evidently reduce global warming potential of rubberized asphalt mixtures but further research is needed to address the acidification potential of nanosilica before industrial-scale utilization of nanosilica additive in pavement construction.